Synthesis of regio- and stereoselectively deuterium-labelled derivatives of L-glutamate semialdehyde for studies on carbapenem biosynthesis. - Ducho, C; Hamed, R; Batchelar, E; Sorensen, J; Odell, B; Schofield, C (2009)
L-glutamate semialdehyde (L-GSA) is an intermediate in biosynthetic pathways including those leading to the carbapenem antibiotics. We describe studies on asymmetric deuteration or hydrogenation of appropriate didehydro-amino acid precursors for the stereoselective synthesis of C-2- and/or C-3-[2H]-labelled L-GSA suitable for use in mechanistic studies. Regioselective deuterium incorporation into the 5-position of L-GSA was achieved using a labelled form of the Schwartz reagent (Cp2Zr2HCl). 4,4-Dideuterated and fully backbone deuterated L-GSAs were prepared. The application of the labelled L-GSA derivatives to biosynthetic studies was exemplified by the chemo-enzymatic preparation of selectively deuterated trans-carboxymethylprolines using two different carboxymethylproline synthases (CarB and ThnE), enzymes that catalyse early steps in the biosynthesis of two carbapenems: (5R)-carbapenem-3-carboxylate and thienamycin, respectively.